The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10157-018-1626-7
|View full text |Cite
|
Sign up to set email alerts
|

GFR estimation in lenalidomide treatment of multiple myeloma patients: a prospective cohort study

Abstract: In our multiple myeloma patient cohort, CKD-EPI and MDRD led to similar CKD staging with minor differences in lenalidomide dosage assignment. Consistent with previous studies, eGFR improved under lenalidomide treatment. To standardize GFR estimation in myeloma patients, we suggest using the CKD-EPI equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Another prospective cohort analysis discovered that CKD-EPI and MDRD formulas had similar CKD staging with small changes in lenalidomide dose adjustment. In another study which designed as prospective cohort found that with CKD-EPI and MDRD formulas had similar CKD staging with minor differences in lenalidomide dosage administration and recommended utilizing the CKD-EPI equation to standardize eGFR calculation in myeloma patients 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Another prospective cohort analysis discovered that CKD-EPI and MDRD formulas had similar CKD staging with small changes in lenalidomide dose adjustment. In another study which designed as prospective cohort found that with CKD-EPI and MDRD formulas had similar CKD staging with minor differences in lenalidomide dosage administration and recommended utilizing the CKD-EPI equation to standardize eGFR calculation in myeloma patients 13 .…”
Section: Introductionmentioning
confidence: 99%